# Solve for g -9/g=-24/(g+5) -9g=-24g+5
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(-9)⋅(g+5)=g⋅(-24)
Solve the equation for g.
Simplify (-9)⋅(g+5).
Apply the distributive property.
-9g-9⋅5=g⋅(-24)
Multiply -9 by 5.
-9g-45=g⋅(-24)
-9g-45=g⋅(-24)
Move -24 to the left of g.
-9g-45=-24g
Move all terms containing g to the left side of the equation.
Add 24g to both sides of the equation.
-9g-45+24g=0
Add -9g and 24g.
15g-45=0
15g-45=0
Add 45 to both sides of the equation.
15g=45
Divide each term by 15 and simplify.
Divide each term in 15g=45 by 15.
15g15=4515
Cancel the common factor of 15.
Cancel the common factor.
15g15=4515
Divide g by 1.
g=4515
g=4515
Divide 45 by 15.
g=3
g=3
g=3
Solve for g -9/g=-24/(g+5)

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top